Серебряный век. Поэзия - Бек Татьяна Александровна (Школа классики, 1999)
Экземпляры: АБ (20200615) / Инвентарный номер: 33781 / Цена: 30.00 / Сис.шифр: 84(2=Рус)53-5 / Авт.знак: С 32 / ББК: 84(2=Рус)53-5